2015
DOI: 10.1589/jpts.27.1937
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flexion-distraction manipulation therapy on pain and disability in patients with lumbar spinal stenosis

Abstract: [Purpose] This study examined the effects of flexion-distraction manipulation therapy on pain and disability in patients with lumbar spinal stenosis. [Subjects] Thirty patients with lumbar spinal stenosis were divided into two groups: a conservative treatment group (n=15) and a flexion-distraction manipulation group (n=15). [Methods] The conservative treatment group received conservative physical therapy, and the flexion-distraction group received both conservative physical therapy and flexion-distraction mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…10 The FMG showed significant decrease in the visual analog scale compared with the CTG. 10 Conservative management of CLDCS includes NSAIDs, patient education, manual therapy, exercise therapy, and physical and rehabilitation activities. 11 The use of the flexion tolerance test has been designed for evaluating patient's pain tolerance and range of motion capacity.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…10 The FMG showed significant decrease in the visual analog scale compared with the CTG. 10 Conservative management of CLDCS includes NSAIDs, patient education, manual therapy, exercise therapy, and physical and rehabilitation activities. 11 The use of the flexion tolerance test has been designed for evaluating patient's pain tolerance and range of motion capacity.…”
Section: Discussionmentioning
confidence: 86%
“…A study by Choi et al involved 30 patients (male = 9, female = 21) who were diagnosed with CLDCS. 10 They were divided into the conservative treatment group (CTG, n = 16) and the flexion-distraction manipulation treatment group (FMG, n = 15). 10 The FMG underwent physical therapy (hot pack [20 min], interferential current therapy [15 min] and ultrasound therapy [5 min]) for 40 minutes per session, followed by 5 episodes of flexion-distraction manipulation therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results suggested that the LSSR can be used for patients with acute lower back pain, or where it is suspected that the nerve root is compromised. The LSSR is useful for improving LF, thus the LSSR can be used to treat spinal canal stenosis when there is limited LF movement 40 ) . This measurement system can also be useful for teaching the LSSR technique to physiotherapy students as a tool for providing feedback with regard to applied forces and relative direction.…”
Section: Discussionmentioning
confidence: 99%